Epicardial implantation of a transvenous implantable cardioverter-defibrillator system in Ebstein's malformation with tricuspid valve repair. Issue 3 (September 2015) - Peng, Ed; Murray, Stephen; Lowrey, Mark; Hasan, Asif
Abstract: In this case report, we describe the implant of a transvenous implantable cardioverter-defibrillator lead on the left ventricular epicardial surface of a young patient with Ebstein's anomaly, facilitating effective defibrillation and anti-tachycardia pacing. The difficulties of conventional placement in Ebstein's malformation as well as the technique and outcome of epicardial lead implantation of a transvenous defibrillator-pacer system are discussed. <Learning objective: This case report highlights the possible placement of a conventional transvenous defibrillator lead on alternative site such as epicardial surface as a solution in patients with Ebstein's anomaly undergoing open heart surgery. This case report also discusses technical challenges, which precluded the transvenous implantation route in a post-operative patient with Ebstein's anomaly. The advantages of epicardial versus subcutaneous system are also discussed.>